A sensitive ultra‐fast liquid chromatography with tandem mass spectrometry method for simultaneous determination of ten constituents of Deng‐Zhan‐Xi‐Xin injection in rat plasma and its application to a comparative pharmacokinetic study in sham and middle cerebral artery occlusion rats. Issue 22 (30th September 2020) - Guo, Xin; Lin, Shan; Liang, Wei; Dou, Xiuxiu; Wang, Xinyu; Tian, Xinhui
Abstract: Deng‐Zhan‐Xi‐Xin injection is widely used to treat cerebrovascular and cardiovascular diseases in clinical practice. A rapid and selective method based on ultra‐fast liquid chromatography with tandem mass spectrometry was established and validated to simultaneously quantify chlorogenic acid, 1, 3‐ O ‐dicaffeoylquinic acid, isochlorogenic acid A, neochlorogenic acid, erigeside I, cryptochlorogenic acid, apigenin‐7‐ O ‐glucuronide, scutellarin, isochlorogenic acid B, and isochlorogenic acid C of Deng‐Zhan‐Xi‐Xin injection in both sham and middle cerebral artery occlusion rats. This was the first quantitative analysis of these ten constituents in both sham and middle cerebral artery occlusion rats. Chromatographic separation of these ten constituents was accomplished on an Acquity HSS T3 column with the mobile phase consisting of acetonitrile and 0.1% formic acid in water. Mass analysis was performed in negative ion mode with an electrospray ionization source using multiple reaction monitoring technology. The pharmacokinetic study of the ten constituents in sham and middle cerebral artery occlusion rats after intravenous administration of Deng‐Zhan‐Xi‐Xin injection was successfully accomplished by using this validated method. Based on the results of pharmacokinetic parameters, significant differences were observed between the two groups, which might be due to the pathological factors of middle cerebral artery occlusion and pharmacological effects of Deng‐Zhan‐Xi‐Xin injection.